A computer based learning resource to support students to learn gas law and kinetic theory of gas - Pratidhina, E (Journal of physics. Conference series, 2019)
Physics is a subject that closely related to nature and being a basic for the development of technology. To give students a real experience, it is suggested to deliver the concept of physics through observation and hands-on experiments. However, some experiments are difficult to be carried out in the classroom. Carrying the experiment on gas law and kinetic theory of gas to the classroom may be challenging. Moreover, in the kinetic theory of gas, microscopic model of gas cannot be observed directly. In this study, we have developed a computer-based learning media that allow students to investigate the ideal gas law through computer simulations. The microscopic model of gas based on theory kinetic gas is also visualized in this computer-based learning media. Students can use this learning resource to help them study gas law and kinetic theory of gas by themselves. The computer-based learning resource is equipped with simulation of experiments, explanation, exercise, and quiz.